Native bee Pollination Ecosystem Services in Agricultural Wetlands and Riparian Protected Lands - Audra L. Hinson; Greg McCarty; Ling Du; Christopher Sichko; Karen Maguire (Wetlands, 2024)
Many freshwater wetlands and riparian systems are protected within agricultural landscapes. Yet, pollinator ecosystem services are seldom considered key ecosystem services provided by these conservation easements. The purpose of this study is to explore the extent of protected aquatic lands to provide pollination ecosystem services by assessing pollinator abundances, crop yield changes, and value estimations of increased soybean yields from a subset of common native solitary bees. We created a novel geodatabase of United States Department of Agriculture (USDA) conservation easements and used this database in the InVEST crop pollination model to model wild solitary bee pollination. We then estimated the monetary value of yield increases provided by pollinators. We found that wetland uplands provided the greatest potential for pollination services for ground nesting bees, followed by herbaceous and forested riparian respectively. Stem nesters preferred forested riparian, then upland habitats. In soybeans fields, we found wild pollinators can provide up to 5.5% yield response from current private aquatic conservation lands. The current landscape is not optimized to use wetlands and riparian conservation lands as pollinator habitat, but these results suggest protected aquatic lands can sustainably increase wild pollination services to agricultural crops if landscapes are managed, protected, and optimized with pollinator services as co-benefit.

Hotspots of wetland loss to impervious surfaces in the conterminous United States - Zhenhua Zou; Chengquan Huang; Megan W. Lang; Ling Du; Greg McCarty; Jeffrey C. Ingebritsen; Jane Harner; Rusty Griffin; Weishu Gong; Jiaming Lu (Science of The Total Environment, 2024)

Topographic Metrics for Improved Mapping of Forested Wetlands - Megan Lang; Greg McCarty; Robert Oesterling; In-Young Yeo (Wetlands, 2013)

Enhanced Detection of Wetland-Stream Connectivity Using LiDAR - Megan Lang; Owen McDonough; Greg McCarty; Robert Oesterling; Bill Wilen (Wetlands, 2012)

Lidar intensity for improved detection of inundation below the forest canopy - Megan W. Lang; Greg W. McCarty (Wetlands, 2009)